Factors Eliciting Corporate Fraud in Emerging Markets: Case of Firms Subject to Enforcement Actions in Malaysia - Ghafoor, Abdul; Zainudin, Rozaimah; Mahdzan, Nurul Shahnaz (Journal of business ethics, 2019)
This study investigates the key factors that elicit financial reporting fraud among companies in Malaysia. Using enforcement action releases issued by the Security Commission of Malaysia (SC) and Bursa Malaysia, we identify a sample of 76 firms that had committed financial reporting fraud during the period of 1996-2016. We use the fraud triangle framework and the Malaysian International Standards on Auditing 240 to identify the factors. Since the simple probit model fails to address the identification problem (partial observability), we estimate our results using a bivariate probit model. The new model estimates the effects of pressure, opportunity, and rationalization on the probability of fraud likelihood by disentangling the detection probability of fraud. Among several proxies used for pressure, our results suggest that aggressive tax reporting and financial difficulties increase the likelihood of fraud commission. In regard to opportunity, we find that dedicated institutional investors, independence of the board, effective audit committee, and the presence of a female on the board provide active monitoring and oversight in reducing fraud occurrence. Results for rationalization suggest that prior violations and frequent changes of external auditors increase the chances of fraud occurrence. This research offers possible insights to auditors, managers, and regulators to prevent, detect, and react to fraud. Specifically, it highlights the specific factors that may exacerbate the fraudulent intentions of firms.